An overview of prevalence, determinants and health outcomes of polypharmacy - Mina Khezrian; Chris J. McNeil; Alison D. Murray; Phyo K. Myint (SAGE Publishing, 2020)
A high rate of polypharmacy is, in part, a consequence of the increasing proportion of multimorbidity in the ageing population worldwide. Our understanding of the potential harm of taking multiple medications in an older, multi-morbid population, who are likely to be on a polypharmacy regime, is limited. This is a narrative literature review that aims to appraise and summarise recent studies published about polypharmacy. We searched MEDLINE using the search terms polypharmacy (and its variations, e.g. multiple prescriptions, inappropriate drug use, etc.) in titles. Systematic reviews and original studies in English published between 2003 and 2018 were included. In this review, we provide current definitions of polypharmacy. We identify the determinants and prevalence of polypharmacy reported in different studies. Finally, we summarise some of the findings regarding the association between polypharmacy and health outcomes in older adults, with a focus on frailty, hospitalisation and mortality. Polypharmacy was most often defined in terms of the number of medications that are being taken by an individual at any given time. Our review showed that the prevalence of polypharmacy varied between 10% to as high as around 90% in different populations. Chronic conditions, demographics, socioeconomics and self-assessed health factors were independent predictors of polypharmacy. Polypharmacy was reported to be associated with various adverse outcomes after adjusting for health conditions. Optimising care for polypharmacy with valid, reliable measures, relevant to all patients, will improve the health outcomes of older adult population.